The role of cannabinoids in pain modulation in companion animals - Miranda-Cortés, Agatha; Mota-Rojas, Daniel; Crosignani-Outeda, Nadia; Casas-Alvarado, Alejandro; Martínez-Burnes, Julio; Olmos-Hernández, Adriana; Mora-Medina, Patricia; Verduzco-Mendoza, Antonio; Hernández-Ávalos, Ismael (Frontiers in Veterinary Science, 2023)
The use of cannabinoids in both veterinary and human medicine is controversial for legal and ethical reasons. Nonetheless, the availability and therapeutic use of naturally occurring or synthetic phytocannabinoids, such as Δ9-tetrahydrocannabidiol and cannabidiol, have been the focus of attention in studies regarding their medical uses. This review aims to examine the role of cannabinoids in pain modulation by analyzing scientific findings regarding the signaling pathways of the endocannabinoid system and discussing the analgesic effects of synthetic cannabinoids compared to cannabinoid extracts and the extent and involvement of their receptors. In animals, studies have shown the analgesic properties of these substances and the role of the cannabinoid binding -1(CB1) and cannabinoid binding -2(CB2) receptors in the endocannabinoid system to modulate acute, chronic and neuropathic pain. This system consists of three main components: endogenous ligands (anandamide and 2-arachidonoylglycerol), G protein-coupled receptors and enzymes that degrade and recycle the ligands. Evidence suggests that their interaction with CB1 receptors inhibits signaling in pain pathways and causes psychoactive effects. On the other hand, CB2 receptors are associated with anti-inflammatory and analgesic reactions and effects on the immune system. Cannabis extracts and their synthetic derivatives are an effective therapeutic tool that contributes to compassionate pain care and participates in its multimodal management. However, the endocannabinoid system interacts with different endogenous ligands and neurotransmitters, thus offering other therapeutic possibilities in dogs and cats, such is the case of those patients who suffer from seizures or epilepsy, contact and atopic dermatitis, degenerative myelopathies, asthma, diabetes and glaucoma, among other inflammatory diseases. Moreover, these compounds have been shown to possess antineoplastic, appetite-stimulating, and antiemetic properties. Ultimately, the study of the endocannabinoid system, its ligands, receptors, mechanism of action, and signaling, has contributed to the development of research that shows that hemp-derived and their synthetic derivatives are an effective therapeutic alternative in the multimodal management of pain in dogs and cats due to their ability to prevent peripheral and central sensitization.